The art of being healthy: a qualitative study to develop a thematic framework for understanding the relationship between health and the arts - Matthew Knuiman; Peter Wright; Michael Rosenberg; Christina R Davies (BMJ Open)
Objective In recent years the health–arts nexus has received increasing attention; however, the relationship is not well understood and the extent of possible positive, negative and unintended outcomes is unknown. Guided by the biopsychosocial model of health and theories of social epidemiology, the aim of this study was to develop a framework pertaining to the relationship between arts engagement and population health that included outcomes, confounders and effect modifiers. A health–arts framework is of value to researchers seeking to build the evidence base; health professionals interested in understanding the health–arts relationship, especially those who use social prescribing for health promotion or to complement treatments; in teaching medical, nursing and health-science students about arts outcomes, as well as artists and health professionals in the development of policy and programmes.Design A qualitative study was conducted. Semistructured interviews were analysed thematically.Setting Western Australia.Participants 33 Western Australian adults (18+ years). Participants were randomly selected from a pool of general population nominees who engaged in the arts for enjoyment, entertainment or as a hobby (response rate=100%).Results A thematic analysis was conducted using QSR-NVivo10. The resulting framework contained seven outcome themes and 63 subthemes. Three themes specifically related to health, that is, mental, social and physical health, while economic, knowledge, art and identity outcomes were classified as health determinants. Within each theme, positive, negative and unintended outcomes (subthemes) were identified and categorised as relating to the individual and/or to the community. A list of confounding and/or effect modifying factors, related to both the arts and health, was identified.Conclusions Given the increasing pressure on health resources, the arts have the potential to assist in the promotion of health and healing. This framework expands on current knowledge, further defines the health–arts relationship and is a step towards the conceptualisation of a causal health–arts model.